Ferroptosis, a Recent Defined Form of Critical Cell Death in Neurological Disorders - Wu, Jia-rui; Tuo, Qing-zhang; Lei, Peng (Journal of molecular neuroscience, 2018)
Ferroptosis is a recently defined form of cell death with the involvement of iron and reactive oxygen species (ROS), which is distinct from apoptosis, autophagy and other forms of cell death. Emerging evidence suggested that iron accumulation and lipid peroxidation can be discovered in various neurological diseases, accompanied with reduction of glutathione (GSH) and glutathione peroxidase 4 (GPX4). In addition, ferroptotic inhibitors have been shown to protect neurons, and recover the cognitive function in disease animal models. This review summarizes the mechanisms underlying ferroptosis and reviews the contributions of ferroptosis in neurodegenerative diseases (i.e. Alzheimer’s disease and Parkinson’s disease), traumatic brain injury, as well as hemorrhagic and ischemic stroke, to provide the current understanding of this novel form of cell death in neurological disorders.